Method for testing bonding strength of substrate structure

By forming a test layer with a low thermal expansion coefficient on the side of the heterogeneous film layer away from the support substrate layer, the bonding strength is judged based on the film layer integrity after the annealing treatment, the problem of limited adhesive bonding strength in the prior art is solved, and the accurate judgment of the bonding strength between the heterogeneous film and the support substrate layer is achieved.

CN119804310APending Publication Date: 2025-04-11SHANGHAI NOVEL SI INTEGRATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510009514.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, due to the limited bonding force between the adhesive and the heterogeneous film layer, it is impossible to accurately judge the bonding strength between the heterogeneous film and the supporting substrate, especially when the bonding strength exceeds the bonding force of the adhesive.

Method used

By forming a test layer on the side of the heterogeneous film layer away from the support substrate layer, the thermal expansion coefficient of the test layer is lower than the thermal expansion coefficient of the heterogeneous film layer, and the bonding strength test results are generated based on the film layer integrity after the annealing treatment.

Benefits of technology

The accurate judgment of the bonding strength between the heterogeneous film layer and the supporting substrate layer is achieved, and the problem of limited adhesive bonding is avoided. The test method is simple and easy to perform, and multiple samples can be tested repeatedly, and the measurement results are highly accurate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804310A_ABST
    Figure CN119804310A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor manufacturing processes, in particular to a method for testing the bonding strength of a substrate structure. The method comprises the following steps that a heterogeneous substrate structure is provided, a test layer is formed on the side, away from a supporting substrate layer, of a heterogeneous thin film layer, the heterogeneous substrate structure with the test layer is obtained, the thermal expansion coefficient of the test layer is lower than that of the heterogeneous thin film layer, and the test layer is used for testing the heterogeneous thin film layer. And carrying out annealing treatment on the heterogeneous substrate structure with the test layer, and generating a bonding strength test result between the heterogeneous thin film layer and the support substrate layer based on the film layer integrity of the heterogeneous substrate structure after annealing treatment. By adopting the method, the bonding strength between the heterogeneous thin film layer and the supporting substrate layer can be accurately judged, and the problem that the bonding strength between the heterogeneous thin film and the heterogeneous substrate cannot be further judged due to the fact that the bonding force between an adhesive and the heterogeneous thin film layer is limited in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor manufacturing technology, and in particular to a method for testing the bonding strength of a substrate structure. Background Art

[0002] Lithium niobate and lithium tantalate are multifunctional crystal materials that integrate piezoelectric, ferroelectric, pyroelectric, acousto-optic and electro-optic properties, and are widely used in acoustic wave devices, optical communications, lasers and optoelectronics. Emerging fields such as 5G, big data, augmented / virtual reality, etc. have put forward higher requirements for information transmission rate, power consumption, and signal quality. In order to prepare devices that can meet the higher requirements of the above emerging fields, piezoelectric materials such as lithium niobate or lithium tantalate are combined with supporting substrates, so that the acoustic wave energy in acoustic devices and the light wave energy in optical devices are more concentrated in the piezoelectric film, which improves the comprehensive performance of the device and is conducive to the miniaturization and integration of the device.

[0003] At present, ion beam stripping and transfer or bonding grinding technology is generally used to transfer heterogeneous films such as lithium niobate or lithium tantalate to a supporting substrate. In order to achieve the transfer of the heterogeneous film to the supporting substrate, the heterogeneous film and the supporting substrate need to have sufficient bonding strength. However, due to the different thermal expansion coefficients between the heterogeneous film and the supporting substrate, the formed bonding structure will debond during the subsequent heat treatment process, resulting in transfer failure. Therefore, the bonding strength between the film and the heterogeneous substrate is crucial to the preparation of the device.

[0004] In the prior art, generally, an adhesive is coated on a heterogeneous film, and the bonding strength between the supporting substrate and the heterogeneous film layer is determined by pulling the heterogeneous film layer coated with the adhesive and testing the pulling force during the pulling process. However, since the bonding force between the adhesive and the heterogeneous film layer is limited, when the bonding strength is greater than the bonding force between the adhesive and the heterogeneous film layer, the bonding strength between the heterogeneous film and the supporting substrate cannot be further determined. Summary of the invention

[0005] In view of the above problems in the prior art, the present application provides a method for testing the bonding strength of a substrate structure, which can accurately determine the bonding strength between a heterogeneous film layer and a supporting substrate layer, and does not have the problem in the prior art that the bonding strength between a heterogeneous film layer and a heterogeneous substrate cannot be further determined due to the limited bonding force between the adhesive and the heterogeneous film layer. The specific technical solution is as follows:

[0006] On the one hand, the present application provides a method for testing the bonding strength of a substrate structure, comprising:

[0007] S1: providing a heterogeneous substrate structure, wherein the heterogeneous substrate structure comprises a supporting substrate layer and a heterogeneous thin film layer located on one side of the supporting substrate layer;

[0008] S2: forming a test layer on a side of the heterogeneous thin film layer away from the supporting substrate layer to obtain a heterogeneous substrate structure having the test layer, wherein the thermal expansion coefficient of the test layer is lower than the thermal expansion coefficient of the heterogeneous thin film layer;

[0009] S3: performing annealing treatment on the heterogeneous substrate structure having the test layer;

[0010] S4: Based on the film layer integrity of the heterogeneous substrate structure after annealing, a bonding strength test result between the heterogeneous film layer and the supporting substrate layer is generated.

[0011] In a possible implementation manner, the test method satisfies at least one of the following characteristics:

[0012] The material of the test layer is metal;

[0013] The support substrate layer comprises at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride and diamond;

[0014] The heterogeneous thin film layer is lithium niobate and / or lithium tantalate.

[0015] In a possible implementation manner, the material of the test layer includes at least one of chromium, tungsten, titanium, molybdenum, platinum and nickel.

[0016] In a possible implementation manner, the test layer is formed by a physical vapor deposition method.

[0017] In a possible implementation manner, the thickness ratio between the test layer and the heterogeneous thin film layer is (0.2-2.5):1.

[0018] In a possible implementation manner, the test method satisfies at least one of the following characteristics:

[0019] The thickness of the test layer ranges from 100 to 1000 nm;

[0020] The thickness of the heterogeneous thin film layer ranges from 100nm to 2000nm.

[0021] In a possible implementation manner, the heterogeneous substrate structure provided in step S1 further includes an oxide layer, and the oxide layer is located between the supporting substrate layer and the heterogeneous thin film layer.

[0022] In a possible implementation manner, the oxide layer has a thickness ranging from 10 to 20000 nm.

[0023] In a possible implementation manner, the annealing treatment includes a first annealing treatment, and the first annealing treatment satisfies at least one of the following characteristics:

[0024] The first annealing treatment uses an annealing temperature of 200 to 400° C. and a holding time of 5 to 60 minutes;

[0025] The heating rate and cooling rate used in the first annealing treatment are not less than 2°C / min.

[0026] In a possible implementation manner, the annealing treatment includes a first annealing treatment and a second annealing treatment in succession, and the annealing temperature used in the first annealing treatment is lower than the annealing temperature used in the second annealing treatment.

[0027] In a possible implementation manner, the first annealing treatment and the second annealing treatment satisfy at least one of the following characteristics:

[0028] The first annealing treatment uses an annealing temperature of 200 to 400° C. and a holding time of 5 to 60 minutes;

[0029] The heating rate used in the first annealing treatment is not less than 2°C / min;

[0030] The second annealing treatment uses an annealing temperature of 300 to 600° C. and a holding time of 5 to 60 minutes;

[0031] The heating rate and cooling rate used in the second annealing treatment are not less than 2°C / min.

[0032] In a possible implementation manner, before forming the test layer on the side of the heterogeneous thin film layer away from the supporting substrate layer, the test method further comprises: performing high temperature treatment on the heterogeneous substrate structure, the temperature used for the high temperature treatment is 350-450°C and the time is 1-5h.

[0033] In a possible implementation manner, the test layer is a metal layer, and the metal layer includes a metal electrode.

[0034] Based on the above technical scheme, the present application has the following beneficial effects: the technical scheme of the present invention provides a method for testing the bonding strength of a substrate structure, the method comprising providing a heterogeneous substrate structure, the heterogeneous substrate structure comprising a supporting substrate layer and a heterogeneous thin film layer located on one side of the supporting substrate layer, forming a test layer on a side of the heterogeneous thin film layer away from the supporting substrate layer, obtaining a heterogeneous substrate structure having a test layer, wherein the thermal expansion coefficient of the test layer is lower than the thermal expansion coefficient of the heterogeneous thin film layer, annealing the heterogeneous substrate structure having the test layer, and generating a thermal expansion coefficient between the heterogeneous thin film layer and the supporting substrate layer based on the film layer integrity of the heterogeneous substrate structure after the annealing treatment. The bonding strength test results of the present invention show that during the annealing process, the test layer will generate a pulling force toward the side of the heterogeneous film layer away from the supporting substrate layer to separate the heterogeneous film layer and the supporting substrate layer. By observing the integrity of the film layer of the heterogeneous substrate structure, the bonding strength between the heterogeneous film layer and the supporting substrate layer can be accurately judged. The testing method of the present invention does not require coating an adhesive on the heterogeneous film layer, and there is no problem of being unable to further judge the bonding strength between the heterogeneous film and the supporting substrate due to the limited bonding force between the adhesive and the heterogeneous film layer. The test method of the present invention is simple and easy to perform, and multiple samples can be tested repeatedly at one time, and the measurement results are highly accurate. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 The figure is a schematic diagram of the steps of a method for testing the bonding strength of a substrate structure in a specific embodiment of the present invention.

[0037] Figure 2 It is a schematic structural diagram of a heterogeneous substrate structure after annealing treatment when the heterogeneous substrate structure does not include a supporting substrate layer in a specific embodiment of the present invention.

[0038] Figure 3 Schematic diagram of the film integrity of the first test group and the second test group in Example 1 of the present invention.

[0039] Figure 4 Schematic diagram of the film integrity of the second test group in Example 1 of the present invention.

[0040] Figure 5 Schematic diagram of the film integrity of the first test group, the second test group and the third test group in Example 2 of the present invention.

[0041] Figure 6Schematic diagram of the steps of the test method in Comparative Example 1 of the present invention.

[0042] In the figure: 101 - supporting substrate layer, 102 - heterogeneous film layer, 103 - oxide layer, 104 - test layer, 105 - tensile rod, 106 - first bonding layer, 107 - second bonding layer. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0044] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0045] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0046] On the one hand, a method for testing the bonding strength of a substrate structure provided in an embodiment of the present application is introduced below, including:

[0047] S1: Figure 1 As shown, a heterogeneous substrate structure a is provided, and the heterogeneous substrate structure a includes a supporting substrate layer 101 and a heterogeneous thin film layer 102 located on one side of the supporting substrate layer 101 .

[0048] Specifically, the preparation method of the heterogeneous substrate structure can be an ion implantation combined with stripping method or an oxygen ion implantation method, etc., and it is sufficient as long as the heterogeneous substrate structure can be prepared. The present invention does not specifically limit the preparation method of the heterogeneous substrate structure a.

[0049] In some embodiments, the support substrate layer 101 includes at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride, and diamond.

[0050] In some embodiments, the heterogeneous film layer 102 is lithium niobate and / or lithium tantalate. Both lithium niobate and lithium tantalate have excellent piezoelectric properties. As thin film layers, they are widely used in sensors, vibrators, filters and other fields. The present invention mainly tests the bonding strength of the bonding structure prepared by the piezoelectric material, and then accurately determines the bonding strength between the heterogeneous film and the heterogeneous substrate. In addition, the heterogeneous film layer 102 is limited to lithium niobate and lithium tantalate, which can make the heterogeneous film layer 102 have a thermal expansion coefficient within a suitable range, wherein the thermal expansion coefficient of lithium niobate at room temperature is 8.5×10 -6 / K, the thermal expansion coefficient of lithium tantalate at room temperature is 1.61×10 -6 / ℃.

[0051] In some embodiments, Figure 1 As shown, the heterogeneous substrate structure a further includes an oxide layer 103, and the oxide layer 103 is located between the supporting substrate layer 101 and the heterogeneous film layer 102. By providing the oxide layer 103, the thermal resistance of the bonding interface can be reduced, and the bonding strength of the heterogeneous substrate structure can be improved, the high temperature and high pressure resistance of the heterogeneous substrate structure can be significantly improved, and the test range of the test method of the present invention is wider.

[0052] In some embodiments, the thickness of the oxide layer 103 is in the range of 10 to 20,000 nm. The thickness of the oxide layer 103 can be any value within the above range, which is not enumerated here. The thickness of the oxide layer 103 is further limited to avoid the problem of reduced bonding strength due to a large thickness of the oxide layer 103. By selecting the thickness of the oxide layer 103 within the above range, the bonding strength of the heterogeneous substrate structure can be guaranteed on the one hand, and the accuracy of the test method can be ensured on the other hand.

[0053] S2: forming a test layer 104 on a side of the heterogeneous film layer 102 away from the supporting substrate layer 101, and obtaining a heterogeneous substrate structure b having the test layer 104, wherein the thermal expansion coefficient of the test layer 104 is lower than the thermal expansion coefficient of the heterogeneous film layer 102; by limiting the thermal expansion coefficient of the test layer 104 to be lower than the thermal expansion coefficient of the heterogeneous film layer 102, the test layer 104 can generate a pulling force toward the side of the heterogeneous film layer 102 away from the supporting substrate layer 101 during the subsequent annealing process to separate the heterogeneous film layer 102 and the supporting substrate layer 101, as shown in FIG. Figure 2 As shown, when the heterogeneous substrate structure does not include the supporting substrate layer 101 , the testing layer 104 in the heterogeneous substrate structure c after annealing can drive the heterogeneous film layer 102 to move upward to separate the heterogeneous film layer 102 and the supporting substrate layer 101 .

[0054] In some embodiments, the material of the test layer 104 is metal. By further limiting the material of the test layer 104 to metal, the thermal expansion coefficient of metal is small, and the tensile force generated by the test layer 104 after subsequent annealing treatment is significantly increased, thereby enabling the test method to measure heterogeneous substrate structures with greater bonding strength.

[0055] Specifically, the material of the test layer 104 includes at least one of chromium, tungsten, titanium, molybdenum, platinum and nickel. The thermal expansion coefficients of chromium, tungsten, titanium, molybdenum, platinum and nickel are much smaller than the thermal expansion coefficient of the heterogeneous film layer 102. In the subsequent annealing process, due to the large difference in thermal expansion coefficients between the above metals and the heterogeneous film layer 102, the test layer 104 can generate a greater pulling force to pull the heterogeneous film layer 102, so that the test method can further measure the heterogeneous substrate structure with greater bonding strength. Preferably, the material of the test layer 104 is chromium.

[0056] In some embodiments, the test layer 104 is formed by physical vapor deposition, which can strengthen the bonding force between the test layer 104 and the heterogeneous film layer 102 and provide good adhesion and stability.

[0057] Specifically, the physical vapor deposition method includes at least one of vacuum evaporation coating, sputtering coating, ion plating, molecular beam epitaxy and pulsed physical vapor deposition.

[0058] Specifically, vacuum evaporation coating includes at least one of resistance evaporation coating, electron beam evaporation coating, induction heating evaporation coating and pulsed laser evaporation coating, sputtering coating includes at least one of DC sputtering, radio frequency sputtering and magnetron sputtering, and ion plating includes at least one of magnetron sputtering ion plating, reactive ion plating, hollow cathode discharge ion plating and multi-arc ion plating.

[0059] In some embodiments, the thickness ratio between the test layer 104 and the heterogeneous film layer 102 is (0.2-2.5): 1. Since there is a difference in thermal expansion coefficient between the test layer 104 and the heterogeneous film layer 102, when the difference is small, the tensile force generated by the test layer 104 is smaller than the bonding force between the heterogeneous film layer 102 and the supporting substrate layer 101, thereby reducing the accuracy of the test method. Therefore, the present invention further limits the thickness ratio between the two to ensure that the tensile force generated by the test layer 104 can separate the heterogeneous film layer 102 and the supporting substrate layer 101, thereby improving the accuracy of the test method.

[0060] In some embodiments, the thickness of the test layer 104 is in the range of 100 to 1000 nm. The thickness of the test layer 104 can be any value within the above range, which is not enumerated here. The thicker the test layer 104 is, the stronger the tensile force it generates. By limiting the thickness range of the test layer 104, it can be ensured that the test layer 104 has a certain tensile force, improve the accuracy of the test method, and also reduce the production cost.

[0061] In some embodiments, the thickness of the heterogeneous film layer 102 ranges from 100 nm to 2000 nm. The thickness of the heterogeneous film layer 102 can be any value within the above range, which is not enumerated here. The smaller the thickness of the heterogeneous film layer 102, the greater the bonding strength between it and the supporting substrate layer 101. By limiting the thickness range of the heterogeneous film layer 102, the bonding strength of the prepared heterogeneous substrate structure is ensured, and the effectiveness of the test method is ensured.

[0062] Exemplarily, when the heterogeneous film layer 102 is lithium tantalate, the thickness of the heterogeneous film layer 102 is 600nm, the test layer 104 is a chromium metal layer, and the thickness of the test layer 104 is 500nm; when the heterogeneous film layer 102 is lithium niobate, the thickness of the heterogeneous film layer 102 is 600nm, the test layer 104 is a chromium metal layer, and the thickness of the test layer 104 is 300nm.

[0063] S3: Figure 1 As shown, the heterogeneous substrate structure b having the test layer 104 is subjected to annealing treatment;

[0064] In some embodiments, the annealing treatment includes a first annealing treatment, and the annealing temperature used in the first annealing treatment is 200-400°C and the holding time is 5-60 minutes. The annealing temperature and the holding time can be any point value within the above range, which are not enumerated here. The higher the annealing temperature, the stronger the tension generated by the test layer 104. By limiting the annealing temperature and the holding time in the first annealing treatment, it is ensured that the test layer 104 can generate sufficient tension to separate the supporting substrate layer 101 and the heterogeneous film layer 102, thereby improving the accuracy of the test method, and at the same time, it can reduce the impurities in the heterogeneous film layer 102 and significantly improve the crystallinity.

[0065] In some embodiments, the heating rate and cooling rate used in the first annealing treatment are not less than 2°C / min. Both the heating rate and cooling rate have an impact on the bonding strength of the heterogeneous substrate structure. It is necessary to select a suitable range of heating rate and cooling rate to avoid obvious thermal stress caused by rapid heating, which may reduce the bonding strength of the heterogeneous substrate structure, thereby improving the accuracy of the test method.

[0066] Specifically, the annealing treatment includes: heating the heterogeneous substrate structure b having the test layer 104 to raise its temperature to a first preset temperature, maintaining the temperature at the first preset temperature for a first preset time, and then cooling the temperature.

[0067] Specifically, the first preset temperature is 200-400°C, the first insulation time is 5-60 minutes, the heating rate to the first preset temperature is not less than 2°C, and the cooling rate in the cooling process is not less than 2°C.

[0068] In some embodiments, the annealing process includes a first annealing process and a second annealing process, wherein the annealing temperature used in the first annealing process is lower than the annealing temperature used in the second annealing process. By performing the annealing process twice, the tensile force of the test layer 104 is made stronger, and a piezoelectric heterogeneous substrate structure with a larger bonding strength can be tested.

[0069] In this embodiment, the annealing treatment includes: heating the heterogeneous substrate structure b having the test layer 104 to raise the temperature to a first preset temperature, keeping the temperature at the first preset temperature for a first preset time, and then heating it again to a second preset temperature, and then cooling it at the second preset temperature for a second preset time, and the second preset temperature is higher than the first preset temperature. Specifically, the first preset temperature is 200-400°C, the first holding time is 5-60min, the heating rate of heating to the first preset temperature is not less than 2°C / min, the second preset temperature is 300-600°C, the second holding time is 5-60min, the heating rate of heating to the second preset temperature is not less than 2°C / min, and the cooling rate during the cooling process is not less than 2°C / min.

[0070] In some embodiments, the annealing temperature used in the first annealing treatment is 200-400°C, and the holding time is 5-60 minutes. The annealing temperature and the holding time can be any point value within the above range, which are not enumerated here. By limiting the annealing temperature and the holding time in the first annealing treatment, it is ensured that the test layer 104 can generate sufficient tension to separate the supporting substrate layer 101 and the heterogeneous film layer 102, thereby improving the accuracy of the test method.

[0071] Specifically, the heating rate used in the first annealing treatment is not less than 2° C. / min. The heating rate is limited to avoid obvious thermal stress caused by rapid heating, which may reduce the bonding strength of the heterogeneous substrate structure and further reduce the accuracy of the test method.

[0072] In some embodiments, the annealing temperature used in the second annealing treatment is 300-600°C, and the holding time is 5-60 minutes. The annealing temperature and the holding time can be any point value within the above range, which are not enumerated here. By limiting the annealing temperature and the holding time in the second annealing treatment, the tensile force generated by the test layer 104 is further increased, and the accuracy of the test method is improved.

[0073] Specifically, the heating rate and cooling rate used in the second annealing treatment are not less than 2°C / min. The heating rate and cooling rate are limited to avoid the problem that the obvious thermal stress caused by the excessively fast cooling rate and the excessively fast heating rate reduces the bonding strength of the heterogeneous substrate structure, thereby reducing the accuracy of the test method.

[0074] In some embodiments, before forming the test layer 104 on the side of the heterogeneous film layer 102 away from the supporting substrate layer 101, the testing method further includes: performing high temperature treatment on the heterogeneous substrate structure a, the temperature used for the high temperature treatment is 250-650°C, and the time is 1-15 hours. The temperature and time used for the high temperature treatment can be any point value within the above range, which are not enumerated here. By performing high temperature treatment on the heterogeneous substrate structure, the bonding strength between the supporting substrate layer 101 and the heterogeneous film layer 102 can be further improved, and the effectiveness and accuracy of the testing method can be improved. Preferably, the temperature used for the high temperature treatment is 350-450°C, and the time is 1-5 hours.

[0075] In some embodiments, the test layer 104 is a metal layer, and the metal layer includes a metal electrode. The metal layer is used as a metal electrode, so that the test layer 104 can not only generate tension, but also be electrified.

[0076] S4: Based on the film integrity of the heterogeneous substrate structure c after the annealing treatment, a bonding strength test result between the heterogeneous film layer 102 and the supporting substrate layer 101 is generated.

[0077] In some embodiments, if the integrity of the film layer does not meet the preset condition, it is determined that the bonding strength of the heterogeneous substrate structure c after annealing is weak, and the preset condition means that the film layer of the heterogeneous substrate structure c after annealing has not fallen off.

[0078] In some embodiments, if the integrity of the film layer meets a preset condition, it is determined that the bonding strength of the heterogeneous substrate structure c after annealing is strong, and the preset condition means that the film layer of the heterogeneous substrate structure c after annealing does not fall off.

[0079] The present invention forms a test layer 104 on the side of the heterogeneous film layer 102 away from the supporting substrate layer 101. During the annealing process, the thermal expansion coefficient of the test layer 104 is lower than the thermal expansion coefficient of the heterogeneous film layer 102. The test layer 104 generates a pulling force toward the side of the heterogeneous film layer 102 away from the supporting substrate layer 101, thereby separating the heterogeneous film layer 102 from the supporting substrate layer 101, and then judging the bonding strength between the heterogeneous film layer 102 and the supporting substrate layer 101. The testing method of the present invention does not require coating an adhesive on the heterogeneous film layer 102, and there is no problem of being unable to further judge the bonding strength between the heterogeneous film layer 102 and the supporting substrate layer 101 due to the limited bonding force between the adhesive and the heterogeneous film layer 102. The test method of the present invention is simple and easy to implement, and multiple samples can be repeatedly tested at one time, and the measurement result has high accuracy.

[0080] The following reference Figure 1-6 The specific embodiments of the present application are introduced in conjunction with the above-mentioned test method for the bonding strength of the substrate structure. The following embodiments describe the technical solution of the present application in more detail, and these embodiments are only used for illustrative purposes, because it is obvious to those skilled in the art to make various modifications and changes within the scope of the disclosure of the present application. The reagents used in the embodiments can be obtained by commercial purchase or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained by commercial purchase.

[0081] Example 1

[0082] This embodiment provides a method for testing the bonding strength of a substrate structure, and the specific steps are as follows:

[0083] S11: preparing a heterogeneous substrate structure by ion implantation combined with a stripping method, wherein the heterogeneous substrate structure comprises a supporting substrate layer 101, a heterogeneous thin film layer 102 and an oxide layer 103, wherein the supporting substrate layer 101 comprises at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride and diamond, the heterogeneous thin film layer 102 is lithium tantalate, the thickness of the heterogeneous thin film layer 102 is 600 nm, and the thickness of the oxide layer 103 is 10 to 20000 nm;

[0084] S12: Divide the heterogeneous substrate structure into two groups, namely a first test group and a second test group, and perform high temperature treatment on the first test group and the second test group. The temperature of the high temperature treatment is 450° C. The high temperature treatment time of the first test group is 5 hours, and the high temperature treatment time of the second test group is 1 hour.

[0085] S12: forming a chromium metal layer with a thickness of 500 nm on the heterogeneous thin film layers 102 of the first test group and the second test group respectively by a physical vapor deposition method;

[0086] S13: heating the first test group and the second test group formed with the chromium metal layer to 350° C. at a heating rate of not less than 2° C., keeping the temperature at 350° C. for 60 min, and then cooling the temperature to room temperature at a cooling rate of not less than 2° C.;

[0087] S14: Observe the integrity of the film layers of the first test group and the second test group to obtain the bonding strength test result between the heterogeneous film layer 102 and the oxide layer 103 .

[0088] In this embodiment, if Figure 3 As shown, the left side is the first test group with a high temperature treatment time of 5 hours, and the right side is the second test group with a high temperature treatment time of 1 hour. The longer the high temperature treatment time, the greater the bonding strength between the heterogeneous film layer 102 and the oxide layer 103, that is, the bonding strength of the first test group is higher than that of the second test group. It can be found from the figure that the film layer of the second test group falls off, while the film layer of the first test group does not fall off, which proves that the test method of the present invention has a certain accuracy, and from Figure 4 It can be seen that the heterogeneous film layer of the second test group has obvious curling and deformation, which proves that the bonding strength of the second test group is weak.

[0089] Example 2

[0090] This embodiment provides a method for testing the bonding strength of a substrate structure, and the specific steps are as follows:

[0091] S11: preparing a heterogeneous substrate structure by ion implantation combined with a stripping method, wherein the heterogeneous substrate structure comprises a supporting substrate layer 101, a heterogeneous thin film layer 102 and an oxide layer 103, wherein the supporting substrate layer 101 comprises at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride and diamond, the heterogeneous thin film layer 102 is lithium niobate, the thickness of the heterogeneous thin film layer 102 is 600 nm, and the thickness of the oxide layer 103 is 10 to 20000 nm;

[0092] S12: Divide the heterogeneous substrate structure into three groups, namely, a first test group, a second test group and a third test group, and perform high temperature treatment on the first test group, the second test group and the third test group. The high temperature treatment time of the three groups is 5 hours. The high temperature treatment temperature of the first test group is 450° C., the high temperature treatment temperature of the second test group is 400° C., and the high temperature treatment temperature of the third test group is 350° C.;

[0093] S12: forming a chromium metal layer with a thickness of 300 nm on the heterogeneous thin film layers 102 of the first test group, the second test group and the third test group respectively by a physical vapor deposition method;

[0094] S13: heating the first test group, the second test group and the third test group on which the chromium metal layer is formed, raising the temperature to 350° C. at a heating rate of not less than 2° C., keeping the temperature at 350° C. for 60 minutes, and then cooling the temperature to room temperature at a cooling rate of not less than 2° C.;

[0095] S14: Observe the integrity of the film layers of the first test group, the second test group, and the third test group to obtain the bonding strength test results between the heterogeneous film layer 102 and the oxide layer 103 .

[0096] In this embodiment, the higher the temperature of the high temperature treatment, the stronger the bonding strength of the corresponding heterogeneous substrate structure. Therefore, the bonding strength of the first test group, the bonding strength of the second test group, and the bonding strength of the third test group decrease in sequence. Figure 5 As shown, the left side is the first test group, the middle is the second test group, and the right side is the third test group. It can be seen from the figure that the film layer of the first test group did not fall off, the film layer of the second test group partially fell off, and the film layer of the third test group mostly fell off, which proves that the testing method of the present invention has high accuracy.

[0097] Comparative Example 1:

[0098] This comparative example provides a test method for testing the bonding strength of a heterogeneous substrate structure using an adhesive in the prior art, and the specific steps are as follows:

[0099] S21: preparing a heterogeneous substrate structure by ion implantation combined with a stripping method, wherein the heterogeneous substrate structure comprises a supporting substrate layer 101, a heterogeneous thin film layer 102 and an oxide layer 103, wherein the supporting substrate layer 101 comprises at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride and diamond, the heterogeneous thin film layer 102 is lithium niobate, the thickness of the heterogeneous thin film layer 102 is 600 nm, and the thickness of the oxide layer 103 is 10 to 20000 nm;

[0100] S22: Divide the heterogeneous substrate structure into two groups, namely a first test group and a second test group. The first test group is subjected to high temperature treatment at a temperature of 450° C. for 5 hours. The second test group is not subjected to high temperature treatment.

[0101] S22: performing a glue coating process on the first test group and the second test group respectively, wherein the glue coating process comprises: coating AB glue on a surface of the side of the heterogeneous film layer 102 away from the supporting substrate layer 101 to form a first adhesive layer 106, and coating AB glue on a surface of the side of the supporting substrate layer 101 away from the heterogeneous film layer 102 to form a second adhesive layer 107;

[0102] S23: The first test group and the second test group are respectively bonded to the tension rod 105, and tension is applied to the tension rod 105 by a tension tester to observe the integrity of the film layer of the heterogeneous substrate structure.

[0103] The heterogeneous substrate structure prepared in this comparative example is as follows Figure 6 As shown, the heterogeneous substrate structure includes a first bonding layer 106, a heterogeneous film layer 102, an oxide layer 103, a supporting substrate layer 101 and a second bonding layer 107, wherein the tension rod 105 is bonded to the first bonding layer 106 and the second bonding layer 107 respectively, and by applying tension to the tension rod 105, the first bonding layer 106 drives the heterogeneous film layer 102 to move toward a side of the heterogeneous film layer 102 away from the supporting substrate layer 101, and the second bonding layer 107 drives the oxide layer 103 to move toward a side of the supporting substrate layer 101 away from the heterogeneous film layer 102, thereby achieving separation between the heterogeneous film layer 102 and the oxide layer 103. In this comparative example, the first test group after high temperature treatment The bonding strength of the first test group is significantly higher than that of the first test group which has not undergone high-temperature treatment. When the tensile force applied to the first adhesive layer 106 and the second adhesive layer 107 in the second test group is greater than 600N, the film layer in the second test group falls off, that is, there is a separation phenomenon between the heterogeneous film layer 102 and the oxide layer 103 in the second test group. At this time, the bonding strength between the oxide layer 103 and the heterogeneous film layer 102 in the second test group is about 10MPa. When the tensile force applied to the first adhesive layer 106 and the second adhesive layer 107 in the first test group is greater than 800N, the first adhesive layer 106 in the first test group falls off, and the bonding strength between the heterogeneous film layer 102 and the oxide layer 103 in the first test group cannot be determined.

[0104] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A method for testing the bonding strength of a substrate structure, characterized in that: include: S1: providing a heterogeneous substrate structure, wherein the heterogeneous substrate structure comprises a supporting substrate layer and a heterogeneous thin film layer located on one side of the supporting substrate layer; S2: forming a test layer on a side of the heterogeneous thin film layer away from the supporting substrate layer to obtain a heterogeneous substrate structure having the test layer, wherein the thermal expansion coefficient of the test layer is lower than the thermal expansion coefficient of the heterogeneous thin film layer; S3: performing annealing treatment on the heterogeneous substrate structure having the test layer; S4: Based on the film layer integrity of the heterogeneous substrate structure after annealing, a bonding strength test result between the heterogeneous film layer and the supporting substrate layer is generated.

2. The testing method according to claim 1, characterized in that: The test method meets at least one of the following characteristics: The material of the test layer is metal; The support substrate layer comprises at least one of silicon, polysilicon, silicon on insulator, sapphire, silicon carbide, silicon carbide on insulator, quartz, aluminum nitride, gallium nitride and diamond; The heterogeneous thin film layer is lithium niobate and / or lithium tantalate.

3. The testing method according to claim 1, characterized in that: The material of the test layer includes at least one of chromium, tungsten, titanium, molybdenum, platinum and nickel.

4. The testing method according to claim 1, characterized in that: The test layer is formed by a physical vapor deposition method.

5. The testing method according to claim 1, characterized in that: The thickness ratio between the test layer and the heterogeneous thin film layer is (0.2-2.5):

1.

6. The testing method according to any one of claims 1 to 5, characterized in that: The test method meets at least one of the following characteristics: The thickness of the test layer ranges from 100 to 1000 nm; The thickness of the heterogeneous thin film layer ranges from 100nm to 2000nm.

7. The testing method according to any one of claims 1 to 5, characterized in that: The heterogeneous substrate structure provided in step S1 further includes an oxide layer, and the oxide layer is located between the supporting substrate layer and the heterogeneous thin film layer.

8. The testing method according to claim 7, characterized in that: The thickness of the oxide layer ranges from 10 to 20000 nm.

9. The testing method according to any one of claims 1 to 5, characterized in that: The annealing process includes a first annealing process, and the first annealing process satisfies at least one of the following characteristics: The first annealing treatment uses an annealing temperature of 200 to 400° C. and a holding time of 5 to 60 minutes; The heating rate and cooling rate used in the first annealing treatment are not less than 2°C / min.

10. The test method according to any one of claims 1 to 5, characterized in that The annealing treatment includes a first annealing treatment and a second annealing treatment that are performed consecutively, and the annealing temperature used in the first annealing treatment is lower than the annealing temperature used in the second annealing treatment.

11. The testing method according to claim 10, characterized in that: The first annealing treatment and the second annealing treatment satisfy at least one of the following characteristics: The first annealing treatment uses an annealing temperature of 200 to 400° C. and a holding time of 5 to 60 minutes; The heating rate used in the first annealing treatment is not less than 2°C / min; The second annealing treatment uses an annealing temperature of 300 to 600° C. and a holding time of 5 to 60 minutes; The heating rate and cooling rate used in the second annealing treatment are not less than 2°C / min.

12. The testing method according to any one of claims 1 to 5, characterized in that: Before forming the test layer on the side of the heterogeneous film layer away from the supporting substrate layer, the test method further comprises: performing high temperature treatment on the heterogeneous substrate structure, the temperature used for the high temperature treatment is 250-600° C. and the time is 1-15 hours.

13. The testing method according to any one of claims 1 to 5, characterized in that: The testing layer is a metal layer, and the metal layer includes a metal electrode.